Spatial-dependent mechanical properties of the heel pad by shear wave elastography. (28th February 2017) - Lin, Che-Yu; Chen, Pei-Yu; Shau, Yio-Wha; Tai, Hao-Chih; Wang, Chung-Li
Abstract: The heel pad plays an important role in gait, and its biomechanical behavior and functionality are determined by its specialized architecture and mechanical properties. The purpose of this study was to apply supersonic shear wave elastography, an ultrasound-based noninvasive modality that can quantitatively estimate the shear stiffness of the tissue, to investigate the spatial-dependent mechanical properties of the heel pad. Measurements were conducted in 40 heel pads of 20 normal participants aged between 20 and 30 years by shear wave elastography. The continuous change in local shear stiffness of the heel pad along the depth direction of the heel pad was measured. The result showed that the mechanical properties of the heel pad were highly heterogeneous but followed a simple and specific pattern that local heel pad shear stiffness was highest beneath the plantar skin and decreased continuously with increasing depth. This finding provides a better understanding of the heel pad biomechanics and basis for further investigation of the heterogeneous properties of the heel pad.